2018
DOI: 10.1007/s12035-018-1073-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Cerebral Infarction After Focal Ischemia Using a New MRI Indicator

Abstract: Prolongation of the T2 relaxation time, an increase in T2-weighted signal intensity (T2-SI), and a decrease in the apparent diffusion coefficient (ADC) calculated from diffusion-weighted images (DWI) on magnetic resonance imaging (MRI) are conventional indicators of the vasogenic (interstitial) or cytotoxic (cellular) cerebral edema that develops after ischemic stroke. However, these parameters obtained on stroke imaging have not given us a precise threshold at which we can determine the viability or vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Patients show hypotonia or loss of muscle tone at the early stage of onset. Most patients will still have different degrees of neurological deficit symptoms even after clinical treatment [9,10] . The clinical treatment of patients with ACI mainly includes anticoagulation, lipid regulation, blood sugar control, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Patients show hypotonia or loss of muscle tone at the early stage of onset. Most patients will still have different degrees of neurological deficit symptoms even after clinical treatment [9,10] . The clinical treatment of patients with ACI mainly includes anticoagulation, lipid regulation, blood sugar control, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, vasogenic edema was also present in animal models, presenting as an increase in ADC and a decline in eADC. The latter two are usually employed to identify the type of edema, and the increase in ADC can be indicative of vasogenic edema [43]. In addition, delayed and scattered bleeding was found in the model group on the seventh day, also a typical manifestation in CVST patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that the occurrence of cytotoxic edema is due to the failure of ionic pump or selective activation of ionic channel, further resulting in loss of steady-state ion gradient. Consequently, extracellular fluid enters the intracellular space [30,31], which is then reduced [32]. The electrical conductivity of the brain tissues is also reduced [27], thus leading to a decline of MIPS in the experimental group.…”
Section: Discussionmentioning
confidence: 99%